2022
DOI: 10.1002/anie.202211570
|View full text |Cite
|
Sign up to set email alerts
|

Spin Effect to Promote Reaction Kinetics and Overall Performance of Lithium‐Sulfur Batteries under External Magnetic Field

Abstract: Lithium-sulfur batteries (LSBs) are still limited by the shuttle of lithium polysulfides (LiPS) and the slow LiÀ S reaction. Herein, we demonstrate that when using cobalt sulfide as a catalytic additive, an external magnetic field generated by a permanent magnet can significantly improve the LiPS adsorption ability and the LiÀ S reaction kinetics. More specifically, the results show both experimentally and theoretically how an electron spin polarization of Co ions reduces electron repulsion and enhances the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 72 publications
0
50
0
Order By: Relevance
“…In the discharge process, there are two obvious plateaus corresponding to the conversion from solid S 8 to liquid Li 2 S 4 and Li 2 S 4 to solid Li 2 S 1/2 . Also, the capacity contributions of these processes are Q 1 and Q 2 , while their theoretical capacities are 418 and 1254 mAh g –1 , respectively. The conversion ability from liquid LiPSs to solid Li 2 S 1/2 can be judged by the value of Q 2 / Q 1 . The Q 2 / Q 1 ratio of Co 3 S 4 /CNTs is 2.86, much larger than those of CNTs (2.54), indicating it is beneficial for Co 3 S 4 to catalyze the conversion from liquid LiPSs to solid Li 2 S 1/2 (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…In the discharge process, there are two obvious plateaus corresponding to the conversion from solid S 8 to liquid Li 2 S 4 and Li 2 S 4 to solid Li 2 S 1/2 . Also, the capacity contributions of these processes are Q 1 and Q 2 , while their theoretical capacities are 418 and 1254 mAh g –1 , respectively. The conversion ability from liquid LiPSs to solid Li 2 S 1/2 can be judged by the value of Q 2 / Q 1 . The Q 2 / Q 1 ratio of Co 3 S 4 /CNTs is 2.86, much larger than those of CNTs (2.54), indicating it is beneficial for Co 3 S 4 to catalyze the conversion from liquid LiPSs to solid Li 2 S 1/2 (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…Lately, Zhang et al employed cobalt sulfide-based sulfur host CNF/CoS x in Li-S batteries and demonstrated that in the presence of an external magnetic field, the lithium polysulfide adsorption ability could be significantly improved. 23 In addition, the Li and S conversion reactions under a magnetic field were also mechanistically investigated in this work. Theoretical results show that in the presence of a magnetic field, the electron spinpolarization in CoS x could weaken the Li-S bond and the largest step in Gibbs free energy change from Li 2 S 4 -Li 2 S 2 to Li 2 S 6 -Li 2 S 4 .…”
Section: Mitigation Shuttle Effectmentioning
confidence: 99%
“…21,22 Recently, the magnetic field has also exhibited its power in preventing the shuttle effect of polysulfide. 23 Besides, some niche external field-assisted batteries, for example, sound-assisted and multiple field-assisted rechargeable batteries, have emerged as increasingly potential strategies for battery performance improvement in the last few years. [24][25][26] When an external field, such as light, 27,28 magnetic, 29 or sound, 24,25 is introduced, the corresponding energy can be incorporated with the battery electric field to regulate electrode reaction kinetics and mass transportation, thus leading to breakthrough achievements in battery systems.…”
Section: Introductionmentioning
confidence: 99%
“…MXenes, a two-dimensional (2D) layered transition-metal carbide or nitride family, have been widely applied in Li–S batteries to suppress the “shuttle effect” and catalyze sulfur redox reactions owing to their metal-like conductivity, abundant surface functional groups, and tunable vacancies or defects. For example, Chen et al discovered that the hydroxyl groups on MXene can be substituents by sulfur and/or sulfides, generating strong Ti–S interactions and effectively inhibiting the “shuttle effect” of polysulfides . Besides, the delocalized electronic density of MXene nanosheet favors efficiently upshift of the d -band center, propelling LiPSs redox reactions. Despite all these advantages, MXenes have a strong adsorption tendency for self-restacking due to the high van der Waals interactions, which inevitably reduces the number of active catalytic sites, impedes ion transfer and electrolyte penetration, and compromises their practical efficiency. Thus, designing a structure-stable MXene-based network with rapid lithium ion transport or exchange is of great importance to propel sulfur redox conversions for realizing high performances.…”
mentioning
confidence: 99%